(untitled) (Research, Society and Development, 2022)
Aim: This paper seeks, through a descriptive quantitative research, to present a comparison between companies that innovated and companies that used financial resources available for this purpose and justify the divergence between the indicators. Methods: This descriptive quantitative research carried out a survey of secondary data made available by IBGE on PINTEC results between 2014 and 2017 and BNDES disbursement data for the same time interval. In possession of the data, filters were applied to segment data of operations with credits classified as innovation, then the percentage was calculated to understand the degree of use of available resources for innovation. Results: The results found indicated that 33.6% of the surveyed companies were innovative in products or processes, data that indicates a reduction in relation to the previous two trienniums. Among these companies, most (89%) used their own resources for the development of activities. Conclusion: We can see a difference in the types of support declared by the indicators and the difficulties pointed out by companies for the implementation of innovation.